Better or worse food: Nutrition value of the prey fishes and the potential health implications for Indo-Pacific humpback dolphins - Lin, Jianqing; Liang, Yan; Zhao, Hancheng; Gutang, Qilin; Wu, Zonghuan; Gao, Yan; Liu, Sailan; Li, Kunhuan; Wu, Yinglin; Zhang, Zonghang; Li, Ping; Liu, Wenhua (Frontiers in Marine Science, 2023)
Introduction Overfishing and climate change have combined to cause fishery stocks to decline and fish community composition to change, further threatening the predation and nutritional health of marine mammals. Methods In this study, we collected potential prey fishes catched by fishermen in six habitats of Indo-Pacific humpback dolphins and analyzed their proximate composition (moisture, water, fat and protein), the fatty acid composition and the amino acid composition to evaluate the possible health effect on humpback dolphins. Results The results showed that the nutritional composition varied significantly with species and locations. Fishes in the families Sciaenidae and Engraulidae displayed richer fatty acid composition, while those in the family Clupeidae had the highest value of amino acid quality index. In Zhuhai, home to the largest Indo-Pacific humpback dolphin population, pelagic/neritic prey fishes possessed lower energy density, PUFA content, PUFA/SFA ratio, DHA content, and EAA content compared to demersal fish, suggesting nutritional stress when there is a dietary switch from demersal to pelagic/neritic fishes in Zhuhai population. Discussion Our study provided a framework, with energy density and fatty acid composition as its most important indicator, for assessment of the marine top predators based on the nutritional composition of their prey fishes and revealed the potential threats. Data here is expected to facilitate the development of scientific programs for successful conservation of not only the Indo-Pacific humpback dolphins, but also other marine top predators, possibly through reconstructing their prey fish’s quantity and quality.